“Землякам політика, а мені здається треба вперед культура і література” (Листи Бориса Лазаревського до Микити Шаповала) - Піскун, В.М. (Сумський історико-архівний журнал, 2010)
The publication have the letters to Borys Lazarevskyi to Mykyta Shapoval, which are stored in the Central State Archives of Supreme of Power and Government of Ukraine. The letters contain important information about his life in exile.